2017
DOI: 10.1007/s10900-017-0317-8
|View full text |Cite
|
Sign up to set email alerts
|

Determining Childhood Blood Lead Level Screening Compliance Among Physicians

Abstract: Childhood Lead Poisoning Prevention Programs throughout the U.S. have addressed childhood lead poisoning by implementing primary and secondary prevention efforts. While many programs have helped increase screening rates, in some states children under the age of six still have not been tested for lead. This study aims to identify the barriers to childhood blood lead testing and develop a strategy to increase the number of children tested. Clark County physicians who work with children six and under were surveye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Findings thus indicate a need to target health care professionals’ attitudes and cultural beliefs about the seriousness of childhood lead poisoning, in order to mitigate the problem of childhood lead poisoning in the United States. Similar to prior work, 18 our research uncovered a common attitude among health care providers that lead poisoning no longer poses a significant public health risk to most children—particularly based on their zip code. Nonetheless, all of the interviewees reported that they understood the serious physical and developmental health problems associated with blood lead poisoning.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Findings thus indicate a need to target health care professionals’ attitudes and cultural beliefs about the seriousness of childhood lead poisoning, in order to mitigate the problem of childhood lead poisoning in the United States. Similar to prior work, 18 our research uncovered a common attitude among health care providers that lead poisoning no longer poses a significant public health risk to most children—particularly based on their zip code. Nonetheless, all of the interviewees reported that they understood the serious physical and developmental health problems associated with blood lead poisoning.…”
Section: Discussionsupporting
confidence: 72%
“…Our work extends prior work that examined barriers to testing by examining knowledge about the prevalence of blood poisoning, attitudes about blood lead screening, and awareness of testing and reporting protocols. 18 Additionally, this work sought to identify current gaps in communication between health care providers and public health professionals regarding childhood lead testing. Findings were guided by the SDoH framework 16 and indicated a general lack of knowledge regarding the low testing rates and/or prevalence of blood lead poisoning among children in Texas.…”
Section: Discussionmentioning
confidence: 99%
“…Medicaid guidelines mandate universal screening of all enrollees at 12 and 24 months. In another study, 48% of doctors in Nevada did not strictly adhere to testing guidelines [41]. These studies, coupled with our findings, suggest that individuals who completely trust and rely on their physician's prompting might not be receiving adequate blood lead testing.…”
Section: Discussionmentioning
confidence: 47%
“…A multivariate sensitivity analysis was used to explore the influence of cost for publicity and management on QALYs gained and ICER of CRC screening in the general population. More expenditure for publicity indicated a better community education, and the operating or administrative expenses were related to the involvement of more physicians 9,28 . In the present study it was assumed that these expenditures per capita would be linearly associated with screening and colonoscopy compliance.…”
Section: Methodsmentioning
confidence: 85%